Figure 14 in New contributions to the marine benthic ciliates from the Antarctic area, including description of seven new species (Protozoa, Ciliophora) - Wilbert, Norbert; Song, Weibo (Zenodo, 2005)
Figure 14. Photomicrographs of (A–I) Strombidium apolatum nov. spec. and (J–N) Heterostentor shenae after protargol impregnation. (A) Dorsal view, to show the gap between the equatorial and ventral kinety (arrow); (B) dorsal view, black arrow marks the macronucleus, whereas the white one indicates the end of ventral kinety; (C) ventral view, white and black arrows point to the kinety-gap and macronucleus, respectively; (D, H) macronucleus; (E) dorsal view, to show the equatorial kinety and the girdle (arrows); (F) ventral view, arrowheads mark the inconspicuous buccal membranelles, whereas the arrow points to the cytopharynx; (G) ventral view, focusing at surface level, arrow indicates the newly formed oral primordium, arrowheads mark the equatorial kinety; (I) ventral view, to show the girdle (black arrows) and the equatorial kinety (white arrows); (J) dorsal side of anterior portion, to show the adoral zone of membranelles; (K, M) ventral view, arrow indicates the proximal end of adoral zone of membranelles, while the arrowheads in (K) mark the suture, where some kineties are shortened; (L) to show some irregularly arranged membranelles (arrows); (N) caudal view, to show the thigmotactic area, where the basal bodies are densely arranged (arrows). : Published as part of Wilbert, Norbert & Song, Weibo, 2005, New contributions to the marine benthic ciliates from the Antarctic area, including description of seven new species (Protozoa, Ciliophora), pp. 935-973 in Journal of Natural History 39 (13) on page 964, DOI: 10.1080/00222930400001509, http://zenodo.org/record/4657793